Representations of Poverty in Videogames - Crowley, Adam. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book argues that videogames address contemporary, middle-class anxieties about poverty in the United States. The early chapters consider gaming as a modern form of slumming and explore the ways in which titles like The Elder Scrolls V: Skyrim and World of Warcraft thematize poverty. The argument turns to the field of literary studies to identify analytical frameworks for addressing and understanding these themes. Throughout, the book considers how the academic area of inquiry known as game studies has developed over time, and makes use of such scholarship to present, frame, and value its major claims and findings. In its conclusion, the book models how poverty themes might be identified and associated for the purpose of gaining greater insights into how games can shape, and also be shaped by, the player's economic expectations. Adam Crowley is Professor of English and Director of Composition at Husson University, USA. He is author of The Wealth of Virtual Nations: Videogame Currencies (2017). .
1. Introduction -- 2. Relative Poverty and Slumming Simulations -- 3. Player Identity and the Conditions of Play -- 4. The Player and Game Studies' Rhetoric of Inclusion -- 5. Human Subjects and Digital Poverty -- 6. Conclusion. .
Keywords: Popular Culture; Computer games-Programming.; Culture and Technology; Popular Culture; Game Development